Analisis Model Pengembangan Telecenter Guna Mewujudkan Desa Pintar di Indonesia - Nurchim Nurchim; Indah Nofikasari (Fountain of Informatics Journal, 2018)
The success of the implementation of smart villages is based on the success of the village in carrying out digital transformation with Information and Communication Technology (ICT) as the driver. As a result, villages need an ICT development center which is better known as telecentre. Telecentres contribute to the social and economic development of villages with ICT as the key. In Indonesia, the establishment of telecentres is increasingly prevalent, but until now it was felt that it still did not show its success. The difficulties that arise are, constraints on information and financial management to pay for connectivity, equipment maintenance and telecentre staff salaries. The purpose of this study is to provide a telecentre development model in the form of a Village-Owned Enterprise based on hybrid organizational theory. This research approach was carried out qualitatively with a case study of Lamahu Village, Bone Bolango, Gorontalo. The process of collecting data through interviews, and the results of interviews were analyzed by interpretation into hybrid organizational theory. The results showed that the telecentre development needs to review 3 aspects, namely (1) the establishment of telecentres must have a mission as a social enterprise engaged in the implementation of ICT-based appropriate technology, (2) telecentres in the form of a legal entities Village Owned Enterprise so that they have the opportunity to obtain financial resources from  external (CSR) and internal (village funds) and finally (3) telecentre human resources must involve the village community from origin so that they can help the effectiveness of interaction and ensure the sustainability of ICT adoption.